STRATEGI PENGEMBANGAN UMKM DENGAN PEMANFAATAN DIGITAL MARKETING DI ERA MODERNISASI (STUDI PADA UMKM LAMINGO97) - Anis Sya’bania; Maulidya Alfi Anita Zain; Agung Winarno; Agus Hermawan (Rafandha Press, 2022)
The rapid development of digital technology has an impact on the world of marketing. Digital marketing allows potential customers to obtain details regarding products and how to transact through internet media. So far, marketing carried out by lamingo97 has not utilized digital marketing, requiring consumers to come directly to available outlets to view products and make transactions in cash. This activity aims to assist Lamingo97 regarding the use of digital marketing as an MSME development strategy. The training and mentoring phase consists of several stages including (1) Introduction to packaging and branding, (2) logo printing on packaging (3) Product photos, (4) Introduction to social media and creating social media accounts, (5) Introduction to marketplaces and product registration on marketplaces such as Gofood. The results of the training and mentoring for UMKM Lamingo97 are: 1. UMKM Lamingo97 has a new packaging with a simpler and more attractive logo. 2. UMKM Lamingo97 has social media and a marketplace as marketing tools. 3. Business owners have the enthusiasm to develop their business, start actively participating in events and are,more confident because their products already have logos easily recognized by the public. 4. Business owners gain knowledge about social media and marketplace management procedures. 5. Business owners know the importance of digital marketing in advancing a business.